Teachers Formation in Higher Education: Some Aspects under the Light of Education-Work Relations - Castro, Rosane Michelli de [UNESP]; Silva, Vandeí Pinto da [UNESP] (Scientific Research Publishing, 2014)
This text is mainly aimed to address essential aspects of teacher formation in the light of education-work relations in the higher education, from our systematic experience in higher education teaching, particularly teaching and research in the field of Didactics discipline. This formulation is justified considering our concern in seeking to situate this discussion in the context of bringing together knowledge areas and the field of teaching knowledge. Still, our choice to develop such an approach in the light of work-education relationship is due to the belief about the possibilities of seeking to overcome the requirements imposed by capitalism to our educational system, within the possible contradictions of these relationships. In this context the teachers’ formation in higher education gains social and strategic importance, taking on the task of forming individuals of “action-reflection-action” in a society established historically based on the social relations which settle in the light of capital’s multiple determinations. It appears that, in this sense, the major confrontations have been given within the discussions about what to prioritize or combine in the list of criteria and content for teacher’s formation. In Didactic, we seek to emphasize discussions that we consider with a philosophical background, referring to the orientation of teaching practice in knowledge of contemporary ideological struggle; socio-historical, referring to the possibility of formation of disciplines, among them Didactic, and curriculums and references to support its guidance in the process of teacher’s formation. This context of discussion is based on the concrete teaching practice with a view to transformation and to search for new syntheses in terms of knowledge and in terms of historical reality. Then therefore, our methodological approach grounded in the dimensions of the same unit: historical materialism as posture, method and as praxis.
Keywords: college education; teacher formation; historical materialism